Functional Selectivity and Antidepressant Activity of Serotonin 1A Receptor Ligands - Chilmonczyk, Zdzisław (Int J Mol Sci, 2015)
Serotonin (5-HT) is a monoamine neurotransmitter that plays an important role in physiological functions. 5-HT has been implicated in sleep, feeding, sexual behavior, temperature regulation, pain, and cognition as well as in pathological states including disorders connected to mood, anxiety, psychosis and pain. 5-HT(1A) receptors have for a long time been considered as an interesting target for the action of antidepressant drugs. It was postulated that postsynaptic 5-HT(1A) agonists could form a new class of antidepressant drugs, and mixed 5-HT(1A) receptor ligands/serotonin transporter (SERT) inhibitors seem to possess an interesting pharmacological profile. It should, however, be noted that 5-HT(1A) receptors can activate several different biochemical pathways and signal through both G protein-dependent and G protein-independent pathways. The variables that affect the multiplicity of 5-HT(1A) receptor signaling pathways would thus result from the summation of effects specific to the host cell milieu. Moreover, receptor trafficking appears different at pre- and postsynaptic sites. It should also be noted that the 5-HT(1A) receptor cooperates with other signal transduction systems (like the 5-HT(1B) or 5-HT(2A/2B/2C) receptors, the GABAergic and the glutaminergic systems), which also contribute to its antidepressant and/or anxiolytic activity. Thus identifying brain specific molecular targets for 5-HT(1A) receptor ligands may result in a better targeting, raising a hope for more effective medicines for various pathologies.